2016
DOI: 10.1371/journal.pone.0161332
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor-A Increases the Aqueous Humor Outflow Facility

Abstract: PurposeAnti-vascular endothelial growth factor (VEGF) antibody therapy is an effective treatment for ocular angiogenesis. Although the intraocular pressure of some patients increases after anti-VEGF therapy, the effects of VEGF-A on the aqueous humor outflow pathway remain unknown. This study investigated the effects of VEGF-A on the aqueous humor outflow pathway.MethodsWe used human recombinant VEGF121 and VEGF165. Trabecular meshwork (TM) and Schlemm’s canal endothelial (SCE) cells were isolated from the eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…Proposed mechanisms include obstruction of the conventional outflow pathway by protein aggregates or foreign particles, 17 or damage to the outflow pathway by local inflammation, 15 mechanical trauma, 18 chronic angle closure, 19 or toxicity following repeated injections. 20 Vascular endothelial growth factor may affect outflow facility 21 and we show in our companion study that endogenous VEGF expression in the trabecular meshwork is a paracrine regulator of conventional outflow facility. 22 Although these studies implicate reduced outflow facility as the mechanism for sustained elevated IOP in patients receiving chronic intravitreal anti-VEGF injections, to our knowledge, outflow facility has not been measured in patients receiving prolonged anti-VEGF injections.…”
mentioning
confidence: 75%
“…Proposed mechanisms include obstruction of the conventional outflow pathway by protein aggregates or foreign particles, 17 or damage to the outflow pathway by local inflammation, 15 mechanical trauma, 18 chronic angle closure, 19 or toxicity following repeated injections. 20 Vascular endothelial growth factor may affect outflow facility 21 and we show in our companion study that endogenous VEGF expression in the trabecular meshwork is a paracrine regulator of conventional outflow facility. 22 Although these studies implicate reduced outflow facility as the mechanism for sustained elevated IOP in patients receiving chronic intravitreal anti-VEGF injections, to our knowledge, outflow facility has not been measured in patients receiving prolonged anti-VEGF injections.…”
mentioning
confidence: 75%
“…94 Animal studies have demonstrated that VEGF increases aqueous humor outflow facility and that blockage of VEGF receptors leads to ocular hypertension. 35 Anti-VEGF inhibition of the disassembly of the endothelial intercellular junctions, decrease in the endothelial fenestrations, and inhibition of nitric oxide production are a few of the biochemical mechanisms that may explain the impaired outflow and sustained rise in IOP.…”
Section: Long-term Effects Of Intravitreal Anti-vegf Injections mentioning
confidence: 99%
“…At indicated time points (0, 2, 4, 6, 8 hr), the TEER was measured by using Millicell-ERS (Millipore, Germany) as previously described [31][32][33]. The TEER were detected and compared as the percent change from corresponding baseline values.…”
Section: Transendothelial Electrical Resistance (Teer) 2 X 10mentioning
confidence: 99%